Aging population in urban India: Challenges and insights from Kolkata - Mazumder, Sreelekha; Shaw, Rajib (International Journal of Social and Administrative Sciences, 2024)
In Kolkata, the elderly people represent 11.76% of the total population. Here we present new data on the aging population of Kolkata, and address its causes, and consequences. We interviewed 110 elderly male and female who are living with their family members and in old age homes in Kolkata. The data was collected from low, medium, and high-income groups from three urban housing societies as well as five old age homes. It has been observed that the elderly male and female of the low-income group have no medical and life insurance, and many of them are suffering from health issues. Although females up to 60 years are part of Self-Help Group, males are suffering from Loneliness. The elderly male and female of the medium, and high-income group do not have financial issues, but most of them do not visit doctors and health care centers for regular health check-ups. Digital literacy has to be improved. Elderly people staying in old age homes are mentally and physically much better than their counterparts who live with family members. Analysis of existing government policies reveal scope for improvement of the elderly people. We propose social innovation for the elderly population in Kolkata.